Dasanama Jarwa of the Terms for 'Parent' (Wong Tuwa) and 'Father' (Bapak) in the Manuscript Sěstra Agěng Adidarma, Pakualaman Collection - Rahmat Rahmat (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2026)
The Javanese linguistic corpus is a field that is constantly being studied and examined, particularly in the context of research. Dasanama is a linguistic concept in the Javanese language that refers to synonyms. This study aims to explore the dasanama jarwa, or the meanings, of the words wong tuwa ‘parent/elders’ and bapak ‘father’. The subject of this study is drawn from a manuscript in the Widyapustaka Pakualaman collection titled Sestra Ageng Adidarma (Pi. 35), which contains the Ajidipa folktale and explains the meanings of the terms wong tuwa and bapak. The term wong tuwa has a counterpart in tiyang sěpuh, which carries a nuance of meaning that differs from its lexical definition (as found in a dictionary). The term wong tuwa implies that a person must be obeyed, whereas tiyang sěpuh implies that a person should be respected even if a misunderstanding occurs. Similarly, the word “bapak” has synonyms such as sudarma, rama, bapa, and yayah. The word sudarma means “blessing from God”; rama implies that a father has a duty to teach his children about religion; bapa refers to the means by which human life is conceived; and yayah which denotes the relationship between father and child, conveys a sense of kinship. Each of these words also conveys an identity—namely, social, spiritual, and natural dimensions. The findings of this study shed new light on the meanings of these words, which may be unfamiliar to the Javanese people today.